TRANSFORMATION OF DIGITAL ZAKAT AND WAKAF: A SYSTEMATIC REVIEW OF INNOVATION MODELS - Cholid Fadil (Penelitian dan Pengembangan Ilmu, 2026)
The global Islamic philanthropy landscape is undergoing a fundamental paradigm shift due to massive digital disruption, transforming traditional zakat and waqf management into integrated, data-driven systems. Despite the vast potential of zakat and waqf, the realization in Indonesia remains below 7% for zakat and 1% for cash waqf, indicating a systemic failure to convert this potential into tangible economic impact. Using a systematic narrative review of literature from Scopus, Web of Science, and Google Scholar databases for the 2014-2024 period, this study synthesizes digital innovation models within a